Instructions to Authors for Use of Open Journal System (OJS) - Philippines, JAFES (Journal of the ASEAN Federation of Endocrine Societies, 2015)
The Journal of the ASEAN Federation of Endocrine Societies (JAFES) is an OPEN ACCESS, internationally peer-reviewed, English language, medical and health science journal that is published two times a year by the ASEAN Federation of Endocrine Societies. It shall serve as the endocrine window between the ASEAN region and the world, featuring original papers and publishing key findings from specialists and experts of endocrinology. Our objective is to transform the JAFES into a self-sustaining, peer-reviewed, English language journal for the ASEAN Federation of Endocrine Societies, publishing high quality research work from its South East Asian members as well as international experts on Endocrinology and Metabolism. The JAFES has migrated to the Online Journal System platform in May 2014. This document outlines the steps to be followed by authors in submitting manuscripts to the Journal of the ASEAN Federation of Endocrine Societies website.